1983
DOI: 10.3109/17453678308992914
|View full text |Cite
|
Sign up to set email alerts
|

The Stress-Protecting Effect of Metal Plates on the Intact Rabbit Tibia

Abstract: The purpose of the present study was to find the extent of stress-protection by a steel plate (45 X 5 X 1 mm) on the rabbit tibia. The animals were sacrificed after 6, 12 and 18 weeks. The median strength after plate application was 84, 73 and 72%. respectively. The elastic stiffness of plated bones was also reduced, while the deformation at fracture showed no significant reduction. The mineral content in the bone segment previously covered by a plate was measured by photon absorptiometry; it was reduced after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…A total joint replacement may lead to a significantly altered stress distribution pattern in the bones, as shown in studies using finite element analysis (Huiskes et al 1987, Om et al 1990, Tissakht et al 1993. Adaptive remodeling with local bone loss has previously been observed in total hip arthroplasty (THA) (Brown andRing 1985, Engh et al 1987), total knee arthroplasty (TKA) (Cameron and Cameron 1987, Mintzer et al 1990, Petersen et al 1995b), spinal fixation (McAfee et al 1989, Smith et al 1991, Dalenberg et al 1993) and rigid metal plating (Terjesen andBenum 1983, Uhthoff et al 1994). This implant-related osteopenia is considered to be mainly a result of stress-shielding, but immobilization, in combination with a local reaction of the tissue to the operative trauma itself, may play a role as well (Frost 1983).…”
mentioning
confidence: 98%
“…A total joint replacement may lead to a significantly altered stress distribution pattern in the bones, as shown in studies using finite element analysis (Huiskes et al 1987, Om et al 1990, Tissakht et al 1993. Adaptive remodeling with local bone loss has previously been observed in total hip arthroplasty (THA) (Brown andRing 1985, Engh et al 1987), total knee arthroplasty (TKA) (Cameron and Cameron 1987, Mintzer et al 1990, Petersen et al 1995b), spinal fixation (McAfee et al 1989, Smith et al 1991, Dalenberg et al 1993) and rigid metal plating (Terjesen andBenum 1983, Uhthoff et al 1994). This implant-related osteopenia is considered to be mainly a result of stress-shielding, but immobilization, in combination with a local reaction of the tissue to the operative trauma itself, may play a role as well (Frost 1983).…”
mentioning
confidence: 98%
“…This was confirmed in the present study, as relatively slight bone changes were found. A median reduction in bending strength and stiffness after 12 weeks of 13.5 and 12.2 per cent, respectively, were found, compared to reductions of the same parameters of about 25 per cent after application of a six-hole steel plate of 5 x 1 mm cross-section (Terjesen & Benum 1983b). Llftman et al (1980) found a reduction in torsional strength of about 50 per cent after application of a considerably more rigid plate (6 X 2 mm cross-section) for 12 weeks.…”
Section: Discussionmentioning
confidence: 95%
“…Llftman et al (1980) found a reduction in torsional strength of about 50 per cent after application of a considerably more rigid plate (6 X 2 mm cross-section) for 12 weeks. Furthermore, the stress-protecting effect occurred even at 6 weeks after plating (Terjesen & Benum 1983b, Llftman et al 1980. Thus, the stress-protecting effect caused by external mini-fixation on intact rabbit tibiae occurs later, and is less pronounced, than that caused by metal plates.…”
Section: Discussionmentioning
confidence: 99%
“…Human growth hormone was used because it is also known to have an effect in lower mammals (Geschwind 1966, Wittbjer et al 1984. The atrophy of diaphyseal bone protected from load and deformation by a rigid internal fixation plate is a result of resorption of cortical bone covered by the plate resulting in widening of the medullary cavity, and decreased strength (Akeson et al 1976, Slatis et al 1978, Stromberg and Dal6n 1978, LBftman et al 1980, Terjesen and Benum 1983, Terjesen et al 1985. After removal of the plate, the atrophied bone will be subjected to an increased loading, a readaptation process occurs, and strength gradually returns (LMman et al 1980).…”
Section: Discussionmentioning
confidence: 99%
“…Rigid internal fixation results in atrophy of diaphyseal bone (Striirnberg and DalCn 1976, 1975, Slatis et al 1978, Terjesen and Benum 1983, Terjesen et al 1985 by protection of the bone from mechanical loading and deformation resulting in decreased torsional strength (Stromberg and Dalen 1976). Recovery of the bone strength occurs following removal of the plate (Lhftman et al 1980).…”
mentioning
confidence: 99%